2001
DOI: 10.1097/00000658-200105000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Are Concerns Over Right Laparoscopic Donor Nephrectomy Unwarranted?

Abstract: ObjectiveTo examine the ability of several large, experienced transplantation centers to perform right-sided laparoscopic donor nephrectomy safely with equivalent long-term renal allograft function. Summary Background DataEarly reports noted a higher incidence of renal vein thrombosis and eventual graft loss. However, exclusion of right-sided donors would deprive a significant proportion of donors a laparoscopically harvested graft. MethodsA retrospective review was performed among 97 patients from seven cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
1
9

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 9 publications
(11 reference statements)
4
64
1
9
Order By: Relevance
“…Moreover, the intraoperative complication rates were similar between left and right donors, and the 3 right procurementtechniques. Our intraoperative complication rates are similar [5] if not better than others have reported [10,19]. We have not seen an increase in intraoperative complications despite the evolution of more technically challenging methods of procurement.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, the intraoperative complication rates were similar between left and right donors, and the 3 right procurementtechniques. Our intraoperative complication rates are similar [5] if not better than others have reported [10,19]. We have not seen an increase in intraoperative complications despite the evolution of more technically challenging methods of procurement.…”
Section: Discussionsupporting
confidence: 81%
“…Dols et al reported 2 conversions in 159 R-LAP-DN [5]. In another series of 97 R-LAP-DN, 3 conversions occurred [19].…”
Section: Discussionmentioning
confidence: 95%
“…Using this modification, they achieved nine additional successful right-sided laparoscopic nephrectomies. More recently, a retrospective North American seven-centre review of 97 right laparoscopic nephrectomies [5] also indicated that successful transplantation are able to be achieved with grafts provided by right living-donor nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Such harvesting of a caval rim does not narrow the inferior vena cava. The implantation operation is also of importance [5]: tension-free anastomoses are best achieved by surgeons who master vascular reconstructions, as these are often more complex than in conventional cadaveric kidney transplantation.…”
mentioning
confidence: 99%
“…First, initial reports suggested higher vascular (6) and ureteral (7) complication rates with laparoscopically procured kidney grafts. But subsequent studies have demonstrated that with increasing surgical experience, low technical complication rates can also be achieved with laparoscopic kidneys, regardless whether left or right kidneys (8), or kidneys with anatomical variations, such as multiple renal arteries, are used (9). Second, several investigators have shown slower early post-transplant function for laparoscopic (vs. open) grafts, as measured by delayed function rates (10)(11)(12) and by the recipients' early post-transplant serum creatinine levels (10,13,14).…”
Section: Introductionmentioning
confidence: 99%